A hit and miss investigation of asymmetries in wheelchair navigation - Nicholls, M.; Hadgraft, N.; Chapman, H.; Loftus, Andrea; Robertson, J.; Bradshaw, J. (Springer New York LLC, 2010)
In contrast to the leftward inattention caused by right parietal damage, normal brain function shows a subtle neglect of the right and left sides in peripersonal and extrapersonal space, respectively. This study explored how these attentional biases cause healthy individuals to collide with objects on the right. In Experiment 1, participants navigated manual and electric wheelchairs through a narrow doorway. More rightward collisions were observed for the electric, but not the manual, wheelchair. Experiment 2 demonstrated that the rightward deviation for electric wheelchairs increased for wider doorways. Experiment 3 established that the rightward deviation is not the result of task-related vestibular input, using a remote control device to operate the wheelchair. The rightward deviation persisted in Experiment 4 when the doorway was removed, suggesting that the bias is the result of a mis-bisection of space. In Experiment 5, the rightward bias was replicated using an electric scooter, which is steered using handlebars. Finally, Experiment 6 required participants to point to the middleof the doorway, using a laser, before moving the scooter. Rightward mis-bisection was observed in both conditions. Rightward mis-bisection of lines in extrapersonal space provides the most parsimonious explanation of the rightward collisions and deviations.